Application of phase equilibrium studies of CaO–SiO2–Al2O3–MgO system for oxide inclusions in Si-deoxidized steels. (March 2020) - Lyu, Sha; Ma, Xiaodong; Chen, Mao; Huang, Zongze; Yao, Zan; Wang, Geoff; Zhao, Baojun
Abstract: In the steelmaking process, the compositions of the oxide inclusions could be modified by refining slags to a large extent. The chemistries of the oxide inclusions and refining slags can be described by the system CaO–SiO2 –Al2 O3 –MgO. Phase equilibria and liquidus temperatures in this system have been experimentally investigated in the composition and temperature ranges related to the oxide inclusions and refining slags by means of high-temperature equilibration, quenching and electron probe X-ray microanalysis. Isotherms in the interval of 20 °C between 1260 and 1560 °C were determined in the primary phase fields of wollastonite, anorthite, spinel, and melilite. Effects of the mass ratio of (Al2 O3 +SiO2 )/((Al2 O3 +SiO2 )+(CaO + SiO2 )) and MgO content on the liquidus temperatures have been discussed to assist inclusion control. To obtain the lowest liquidus temperature of Al2 O3 –SiO2 –CaO–MgO system inclusions, refining time ought to be properly controlled.